2023
DOI: 10.1371/journal.pone.0285498
|View full text |Cite|
|
Sign up to set email alerts
|

Environmental and climate variability drive population size of annual penaeid shrimp in a large lagoonal estuary

Abstract: Species with short life spans frequently show a close relationship between population abundance and environmental variation making these organisms potential indicator species of climatic variability. White (Penaeus setiferus), brown (P. aztecus), and pink (P. duorarum) penaeid shrimp typically have an annual life history and are of enormous ecological, cultural, and economic value to the southeastern United States and Gulf of Mexico. Within North Carolina, all three species rely on the Pamlico Sound, a large e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Duggan et al (2019) explained that unlike in places with no freshwater inflow (high salinity), the density of prawns increases. Salinity is a factor that determines the abundance, survival, recruitment, osmotic pressure, and distribution of penaeid prawns in waters (Torres et al 2020;Yang et al 2020;Minello 2017;Jiang et al 2021;Plagányi et al 2021;Rahi et al 2021;Amalia et al 2022;Azwar et al 2023;Schlenker et al 2023).…”
Section: Density Distribution Of Penaeus Merguensis De Man 1888 Based...mentioning
confidence: 99%
“…Duggan et al (2019) explained that unlike in places with no freshwater inflow (high salinity), the density of prawns increases. Salinity is a factor that determines the abundance, survival, recruitment, osmotic pressure, and distribution of penaeid prawns in waters (Torres et al 2020;Yang et al 2020;Minello 2017;Jiang et al 2021;Plagányi et al 2021;Rahi et al 2021;Amalia et al 2022;Azwar et al 2023;Schlenker et al 2023).…”
Section: Density Distribution Of Penaeus Merguensis De Man 1888 Based...mentioning
confidence: 99%
“…EBFM is widely viewed as a set of tools for successful management in different contexts (Trochta et al 2018) and constitutes a fundamental component of sustainability and balance between environmental, social, and economic objectives (Marshall et al 2018). Current stock assessment frameworks often do not include key features such as ecosystem components and ecological complexity of popu-lations, although it has already been shown that environmental and climatic variation are closely associated with the abundance variation of commercially important species (e.g., Schlenker et al 2023). However, the ongoing development of next-generation stock assessments highly prioritizes the incorporation of missing critical information (Punt et al 2020).…”
Section: Introductionmentioning
confidence: 99%